What Happens from the Foundation of the World? A Crux Interpretum in Revelation 13:8 - NAGY, József (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2024)
The phrase ἀπὸ καταβολῆς κόσμου in Revelation 13:8 can be interpreted and translated in two ways. First, the Lamb-Christ was slain since the creation. Second, the worshippers of the beast have been missing from the Book of Life since the beginning. The main problem arises from the fact that the phrase ἀπὸ καταβολῆς κόσμου immediately follows τοῦ ἐσφαγμένου, which points to the lamb. Although the proponents of this reading list many other arguments, the literal proximity provides the basis for all other ideas. However, if we look at the problem from a broader perspective, the conclusion is different. For example, Revelation 13:7–10 focuses on the relationship between the beast and humanity. It can be seen that the section does not centre on the Lamb. Further changes of perspective confirm that ἀπὸ καταβολῆς κόσμου refers to individuals not mentioned in the Book of Life (e.g. Rev 17:8).